Improved kidney graft function after preservation using a novel hypothermic machine perfusion device. - Maathuis, M; Manekeller, S; van der Plaats, A; Leuvenink, H; 't Hart, N; Lier, AB; Rakhorst, G; Ploeg, R; Minor, T (2007)
OBJECTIVE: To study graft function and ischemia/reperfusion injury of porcine kidneys after preservation with the new Groningen Machine Perfusion (GMP) system versus static cold storage (CS). INTRODUCTION: The increasing proportion of marginal and nonheart beating donors necessitates better preservation methods to maintain adequate graft viability. Hypothermic machine preservation (HMP) is a promising alternative to static CS. We have therefore developed and tested an HMP device, which is portable and actively oxygenates the perfusate via an oxygenator. The aim of the present study was to examine the efficacy of the GMP system in a transplantation experiment. MATERIALS AND METHODS: In a porcine autotransplantation model, kidneys were retrieved and either cold stored in University of Wisconsin CS for 20 hours at 4 degrees C or subjected to HMP using University of Wisconsin machine perfusion at 4 degrees C with 2 different pressure settings: 30/20 mm Hg or 60/40 mm Hg. RESULTS: HMP at 30/20 mm Hg was found to better preserve the viability of kidneys reflected by improved cortical microcirculation, less damage to the proximal tubule, less damage mediated by reactive oxygen species, less proinflammatory cytokine expression, and better functional recovery after transplantation. However, high perfusion pressures (60/40 mm Hg) resulted in higher expression of von Willebrand factor and monocyte chemotactic peptide-1 in postpreservation biopsies and subsequent graft thrombosis in 2 kidneys. CONCLUSIONS: It is concluded that the GMP system improves kidney graft viability and perfusion pressures are critically important for outcome.